Genetic algorithm-tabu search for mobile agents measurement scheduling in wireless sensor networks - WANG Sheng; WANG Xue; BI Dao-wei (Tongxin xuebao)
A mixed strategy for mobile agents measurement scheduling in WSN was proposed, which was combined by genetic algorithm and tabu search. The proposed scheduling strategy takes the creation sequence, priority and energy consumption of mobile agents into consider, for reasonablely dispatching multiple mobile agents and ensuring the meas- urement performance of WSN. Simulation results demonstrate that the proposed algorithm can effectively arrange the order of mobile agents dispatching, where the energy consumption and time delay can be remarkablely decreased and the lifetime of WSN can be accordingly prolonged.